2000
DOI: 10.1128/jvi.74.7.3313-3320.2000
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Spike Protein VP4 Is Present at the Plasma Membrane and Is Associated with Microtubules in Infected Cells

Abstract: VP4 is an unglycosylated protein of the outer layer of the capsid of rotavirus. It forms spikes that project from the outer layer of mature virions, which is mainly constituted by glycoprotein VP7. VP4 has been implicated in several important functions, such as cell attachment, penetration, hemagglutination, neutralization, virulence, and host range. Previous studies indicated that VP4 is located in the space between the periphery of the viroplasm and the outside of the endoplasmic reticulum in rotavirus-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 40 publications
8
60
3
Order By: Relevance
“…3). The mixed pattern of VP4 that has been previously reported (15,24), which consists of perinuclear ring-like or semicircular structures closely associated to viroplasms (15) and a filamentous array due to its association with microtubules (24), was observed in cells transfected with the control siRNA and siRNA VP7 ; however, in the presence of siRNA NSP4 , most of the perinuclear structures disappeared while the filamentous signal of VP4 remained and was even more evident than that of control cells (Fig. 3).…”
Section: Resultssupporting
confidence: 52%
“…3). The mixed pattern of VP4 that has been previously reported (15,24), which consists of perinuclear ring-like or semicircular structures closely associated to viroplasms (15) and a filamentous array due to its association with microtubules (24), was observed in cells transfected with the control siRNA and siRNA VP7 ; however, in the presence of siRNA NSP4 , most of the perinuclear structures disappeared while the filamentous signal of VP4 remained and was even more evident than that of control cells (Fig. 3).…”
Section: Resultssupporting
confidence: 52%
“…However, neither the targeting of VP4 to the cell surface nor the association of VP4 with rafts was modified by the drug, demonstrating that the fate of VP4 was independent of the accumulation of immature viral particles within the ER. The presence of VP4 on the cell surface of MA 104 cells (26) and at the apical pole of Caco-2 cells (32) has already been observed. In this study, analysis by flow cytometry clearly showed that TM did not prevent VP4 trafficking to the cell surface.…”
Section: Vol 78 2004 Rotavirus Vp4 Assembly Requires Post-er Event mentioning
confidence: 85%
“…These observations include electron cryomicroscopy reconstructions showing a VP4 domain buried beneath the VP7 layer (58), immunoelectron microscopy localizing VP4 in the cytoplasm between viroplasms and the ER membrane (46), colocalization of VP4 with NSP4 by immunofluorescence microscopy and biochemical assays (26), the detection of VP4 in transiently enveloped particles (48), and the accumulation of viral particles in the ER of infected cells depleted of VP4 by small interfering RNA (11). On the other hand, immunofluorescence microscopy using monoclonal antibody 7.7 detects VP4 in lipid rafts, bound to cytoskeletal elements, and exposed on the external face of the apical plasma membrane (14,38,52). This antibody does not detect VP4 in the ER lumen.…”
Section: Discussionmentioning
confidence: 99%